Correlación entre el método geogauge y el método del cono de arena para determinar la densidad del suelo en campo (2012)
In the following lines which will be summarized in detail the process was run to achieve the main objective of this research. To carry out the development of a correlation statistic need of a number of field measurements obtained through the implementation of each of the methods well as sand cone as geogague, which gave us the necessary information for establishing the degree of concordance between the measured density with the sand cone stiffness and measured with geogauge. This required first characterize the soil with which trabao through laboratory tests such as, grain size, sand cone test, test geogauge, modified proctor test, CBR test. After having the basic characteristics of the soil, proceeded to build five equal-sized square sections, in this case the sections were built two meters long and two meters wide, with a thickness of 15 cm, each starting with different humidity humidity of 5%, 6%, 7%, 8%, 9%, each leg is compact with a device known as a mini road roller type "frog", making the establishment of a uniform and continuous layer effects have a high quality measurement with both methods. After the first section built proceeded to take measurements, built each section was taken under the following parameter measurements, 20 measurements with each method geogauge 3 measurements with sand cone, this process must be repeated for each of the 5 sections that were prepared with different humidities. Since the sections were square was due to follow a common pattern for measurement, this pattern measurement type is described as "snail" is, was chosen one of the four corners of the stage and starts with geogauge measurements one after another about 40 cm away from each other in sequence from the outermost part of the section on directions clockwise, towards the inner part of the leg or center, resulting in a spiral. During this process goes moisture controlling materials through parallel testing of humedometro or speedy, with which ensures that the measurement is being given under the correct soil moisture and for each tranche. Following this standard measure for all sections for both measurements with measurements geogauge to sand cone culminates making process field data, which is then tabulated and processed as a cloud data Minitab software known as which with based on statistical foundations can relate two different data sets from two different magnitudes in this case would be the magnitudes measured soil stiffness with another serious geogauge and soil density measured by the method sand cone, after which both relate sets a variable function being explained in another, this operation is thrown as a mathematical model is known as is the statistical correlation, which allowed us to reproduce the measured values of rigidity and obtain through this density values.